Strengthening whistleblower protection through legal reform and Islamic ethics in combating corruption in public institutions - Ansori, Ansori (Journal of Islamic Economics Lariba, 2025)
IntroductionWhistleblowers serve as pivotal actors in exposing corruption within governmental and institutional systems. While Indonesia has formal legal instruments aimed at protecting whistleblowers, practical challenges persist, and public perception continues to discourage reporting. Despite Islamic ethical teachings that support moral intervention, cultural and institutional obstacles remain unaddressed. This study investigates whistleblower protection in Indonesia from both legal and Islamic economic perspectives.ObjectivesThe study aims to evaluate the effectiveness of whistleblower protection regulations in Indonesia, identify legal and institutional gaps, and explore how Islamic ethical principles can support and enhance existing mechanisms to promote ethical reporting and institutional accountability.MethodUsing a qualitative research approach, this study applies a structured literature review of statutory laws, academic publications, institutional documents, and comparative international frameworks. It integrates positive legal analysis with normative Islamic economic thought to assess the institutional and cultural readiness of Indonesia to protect and empower whistleblowers in corruption-related cases.ResultsThe study reveals that while legal frameworks such as Law No. 31 of 2014 offer formal protection, enforcement is weak, jurisdictional overlaps exist, and regional implementation is inconsistent. Institutions like the LPSK and KPK lack adequate coordination and resources, particularly outside Jakarta. Public stigma against whistleblowers remains high. Comparative analysis shows that countries with clear reporting procedures and strong enforcement offer better protection. Islamic ethical principles such as justice (adl), accountability (mas’uliyyah), and public welfare (maslahah) can serve as normative frameworks to strengthen public trust and ethical motivation for whistleblowing.ImplicationsThe findings suggest that whistleblower protection in Indonesia requires a multidimensional reform strategy involving legal precision, institutional capacity building, and cultural transformation. Incorporating Islamic values into education, legal discourse, and institutional governance may promote greater societal acceptance and operational effectiveness of whistleblower mechanisms.Originality/NoveltyThis study offers a unique contribution by synthesizing legal analysis with Islamic ethical principles to propose a hybrid framework for whistleblower protection. It highlights the necessity of culturally grounded legal reform in Muslim-majority contexts and provides actionable recommendations for legal, institutional, and educational policy development.